FACTORS CORRELATED WITH THE LENGTH OF STAY OF PATIENTS IN THE EMERGENCY DEPARTMENT OF HOSPITAL A, EAST JAVA - Imowanto, Yuddy; Setijowati, Nanik; irsan , Istan Irmansyah; Triyuliarto, Dwiwardoyo; Johannes, Jeffrey (Fakultas Kedokteran Universitas Sriwijaya, 2025)
The issue of overcrowding in the Emergency Department (ED) has not been resolved in Indonesia, which can be caused by prolonged Length of Stay (LOS) of patients in the ED, resulting in delayed service time and increased mortality rates in the ED. Methods: This research is quantitative research using primary data. The research design used observational analytics with a prospective cohort approach with a sample size of 62 patients. Research Findings: Triage, length of diagnostic testing, the number of patients in the ED at the time the patient arrives, and the nurse-to-patient ratio do not have a significant correlation with ED LOS. There is a significant correlation between Boarding Time and ED LOS (p<0.001) with strong correlation strength (0.77). Conclusions: There is a strong positive linear correlation between Boarding Time and the length of time patients stay in the ED (p<0.001) with strong correlation strength (0.77) and is a dominant factor with a capacity of 58.6% to explain patient’s ED LOS.